Web-based support for daily functioning of people with mild intellectual disabilities or chronic psychiatric disorders: A feasibility study in routine practice - Jessica de Wit; Els Dozeman; Jeroen Ruwaard; Jan Alblas; Heleen Riper (Internet Interventions, 2015)
Background: People with mild intellectual disabilities or chronic psychiatric disorders often experience challenges in important aspects of life and need support in daily functioning. In this study, we examined the feasibility of a web-based program enabling professional support of patients with chronic conditions in their daily functioning. Method: A triangulated research method was applied involving a combination of the results of semi-structured interviews and standardized questionnaires. We conducted face-to-face interviews with clients (n = 11) and telephone interviews with coaches (n = 10) on their initial experiences with the program. In addition, clients took an online pre-test (n = 39) – post-test questionnaire (n = 30) which measured quality of life, empowerment, mastery, social cohesion and satisfaction with care. Clients and coaches both received a questionnaire to report on the perceived usability of the program. Results: Clients and coaches used the program and were positive about this new way of communicating. Clients were pleased that they could contact the coach at any time and experienced increased control over the support they received. Coaches reported positive effects on the levels of independence among clients, saved time and experienced greater flexibility in their scheduling. The implementation of the program did not lead to changes in quality of life, empowerment, mastery, social cohesion or satisfaction with care. Clients and coaches reported that the usability of the MPC could be improved through the use of an enhanced Internet connection. Conclusion: The initial results of the use of web-based support for this client population seem promising and justify further research on online support for clients with mild intellectual disabilities or chronic psychiatric disorders.